Endovascular Treatment of the Tentorial Dural Arteriovenous Fistulas. Case Series and Literature Review - Dmytro V. Shchehlov; Oleh Ye. Svyrydiuk; Svitlana V. Chebanyuk; Igor V. Altman; Olena F. Sydorenko; Mykola B. Vyval; Maryna Yu. Mamonova (Ukrainian Journal of Cardiovascular Surgery, 2024)
Dural arteriovenous fistulas (DAVFs) are vascular anomalies where arteries from the carotid or vertebral arteries directly drain into the dural venous sinuses. Symptoms can range from asymptomatic to severe, including hemorrhage, venous hypertension, and neurological deficits. Tentorial dural arteriovenous fistulas (TDAVFs), a rare subset occurring in the tentorium, represent up to 4% of all DAVFs. Traditionally, DAVFs have been treated surgically, but recent advancements in endovascular embolization have made it a first-line treatment, although the optimal approach is still debated.The aim. To evaluate the efficacy and outcomes of endovascular treatment for TDAVFs.Materials and methods. Between 2012 and 2024, 174 patients with DAVFs were treated at the ScientificPractical Center of Endovascular Neuroradiology of the NAMS of Ukraine, including 8 patients with TDAVFs (mean age 58.5 years). All the patients with TDAVFs were symptomatic, with symptoms including hemorrhage (37.5%), headache, tinnitus, and seizures (62.5%). Endovascular treatment used liquid embolic agents and coils when required. Outcomes were assessed using postoperative angiograms and the modified Rankin Scale.Results. Nine embolization sessions were performed; of these, 8 (88.9%) using n-butyl cyanoacrylate Histoacryl and 1 (11.1%) using Onyx. Complete shunt elimination was achieved in 75% of sessions; 25% had residual lowflow shunting, with vessels unsuitable for further catheterization. No neurological deterioration occurred. The mean length of hospital stay was 5.5 days. Follow-up angiography in 7 patients showed one case of symptom worsening and vessel recruitment, which was later fully treated with repeat transvenous embolization.Conclusions. Endovascular embolization is an effective and safe treatment for TDAVFs. This case series indicates its efficacy but underscores the need for further randomized trials to compare all treatment modalities for tentorial and other deep-seated dural vascular lesions.